Identification of Twelve Different Mineral Deficiencies in Hydroponically Grown Sunflower Plants on the Basis of Short Measurements of the Fluorescence and P700 Oxidation/Reduction Kinetics - Schansker, Gert; Ohnishi, Miho; Furutani, Riu; Miyake, Chikahiro (Frontiers in Plant Science, 2022)
The photosynthetic electron transport chain is mineral rich. Specific mineral deficiencies can modify the electron transport chain specifically. Here it is shown that on the basis of 2 short Chl fluorescence and P700+ measurements (approx. 1 s each) it is possible to discriminate between 10 out of 12 different mineral deficiencies: B, Ca, Cu, Fe, K, Mg, Mn, Mo, N, P, S, Zn. B- and Mo-deficient plants require somewhat longer measurements to detect the feedback inhibition they induce. Eight out of twelve deficiencies mainly affect PS I and NIR-measurements are, therefore, very important for this analysis. In Cu- and P-deficient plants electron flow from the plastoquinone pool to PS I is affected. In the case of Cu-deficiency due to the loss of plastocyanin and in the case of P-deficiency probably due to a fast and strong generation of Photosynthetic Control. For several Ca-, K- and Zn-deficient plant species higher levels of reactive oxygen species have been measured. Here it is shown that this not only leads to a loss of Pm (maximum P700 redox change) reflecting a lower PS I content, but also to much faster P700+ re-reduction kinetics during the I2-P ( 30-200 ms) fluorescence rise phase. The different mineral deficiencies affect the relation between the I2-P and P700+ kinetics in different ways and this is used to discuss the nature of the relationship between these two parameters.